127 A retrospective observational study investigating hypertensive heart disease in an ethnically diverse south-east london population. (6th June 2022) - wisenfeld paine, gabriel; So, Alfred; Page, Thomas; Dalton, Richard; Finnegan, Ciaran; Nageye, Fatuma; Chan, Terrence; Umeojiako, Wilfred; Alfakih, Khaled
Abstract : Introduction: ESC guidelines emphasise the importance of an aetiology-based approach for the diagnosis and treatment of heart failure. Hypertension is a highly prevalent comorbidity in the heart failure cohort and a significant, potentially reversible, cause of heart failure. Although commonly associated with diastolic impairment, hypertensive heart disease also causes left ventricular systolic dysfunction. We sought to assess the aetiologies of heart failure in our ethnically diverse heart failure with reduced ejection fraction (HFrEF) cohort, specifically assessing the prevalence of hypertensive heart disease, and further characterising this cohort with respect to both demographics and diagnostic imaging. Methods We retrospectively searched our HFrEF database and included all patients with a new diagnosis of heart failure and an LVEF < 50% from April 2019 – April 2020. Descriptive data analysis was undertaken; statistical analysis was by paired t-test. Results 363 patients met inclusion criteria. 73.8% were male. Mean age was 66 years. Of the total population, 58% were White, 26% Black, 5% Asian, and 12% 'Other'. 65% had comorbid hypertension. The majority of patients with HFrEF had an ischaemic aetiology (41%), followed by dilated cardiomyopathy (38%), hypertensive heart disease (16%), valvular disease (3%), and other (2%). In the hypertensive cardiomyopathy group, 50% of patients were Black, 38% White, 2% Asian, and 10% 'Other'. All patients in this cohort had undergone echocardiography, 70% had cardiac MRI (cMRI), 35% had invasive angiography, and 7% had CT coronary angiograms (CTCA). The hypertensive cardiomyopathy cohort had a mean LVEF of 27% and 30% on echo and cMRI, respectively; the difference was statistically significant (p value=0.004). LVH was identified in 58% and 65% of these patients on echo and cMRI, respectively. A dilated ascending aorta was identified in 3.8% and 20% of these patients on echo and cMRI, respectively. 55% had no late gadolinium enhancement on cMRI; 45% had a non-ischaemic pattern of enhancement. T1 mapping and extracellular volume (ECV), the newer measurements of myocardial fibrosis and markers of an adverse prognosis, were measured in 18% and 8% of patients undergoing cMRI, respectively; T1 value and ECV were raised 43% and 33% of the time when measured, respectively. Of those who underwent invasive angiography or CTCA only 1 patient had significant coronary artery disease. cMRI did not reveal any inducible ischaemia in those undergoing stress perfusion testing. Conclusion: Hypertensive heart disease is a common cause of HFrEF in our patient population, particularly in those from African/Afro-Caribbean descent. This cohort have heterogenous diagnostic imaging findings and rarely have significant concomitant coronary artery disease, contrary to previous studies. Early identification and aggressive management of hypertensive heart disease is key to preventing the development of HFrEF. Conflict of Interest: N/A